A case of high‐grade pancreatic intraepithelial neoplasia concomitant with type 1 autoimmune pancreatitis: The process underlying both conditions. Issue 3 (5th February 2019) - Sugiyama, Tomoko; Tajiri, Takuma; Hiraiwa, Shinichiro; Machida, Tomohisa; Ito, Hiroyuki; Yoshii, Hisanori; Izumi, Hideki; Nomura, Eiji; Mukai, Masaya; Nakamura, Naoya
Abstract : We report a case of high‐grade pancreatic intraepithelial neoplasia (PanIN) concomitant with lymphoplasmacytic sclerosing pancreatitis. The patient was an 82‐year‐old man in whom narrowing of the main pancreatic duct was detected incidentally by abdominal ultrasonography. Magnetic resonance cholangiopancreatography further revealed abrupt narrowing plus distal dilatation of the duct, from the pancreatic body to the tail. Distal pancreatectomy was performed under a preoperative diagnosis of intraductal papillary‐mucinous neoplasm. Macroscopic examination of the surgical specimen showed an ill‐demarcated, white‐gray area and prominent pancreatic atrophy, while histological analysis detected small (<5 mm in diameter) cystic dilatations of the main pancreatic duct and some branch ducts plus pancreatic atrophy with fibrosis and fatty replacement of acinar cells. We also detected variously sized papillary projections, fused glands, and scattered focal papillary proliferation of columnar ductal epithelium comprising cells with elongated, mildly hyperchromatic nuclei, consistent with high‐grade PanIN. In addition, we observed marked lymphoplasmacytic infiltration, periductal storiform fibrosis, and obliterative phlebitis. Immunohistochemical staining revealed abundant immunogloblin G4‐positive plasma cells, indicative of type 1 autoimmune pancreatitis (AIP). The coexistence of high‐grade PanIN and marked lymphoplasmacytic infiltration, typical of AIP, point to a close association between the former, as a carcinogenic process, and the latter, as an immune response.